Chile : Selected Issues. (IMF Staff Country Reports; Country Report, 2001)
This paper presents four studies on selected issues of the Chilean economy. The new framework for fiscal policy represented by the authorities' target of a central government structural surplus of 1 percent of GDP is also discussed. This study examines whether the variance of the cyclical component of output in Chile and 11 other countries increased during the 1990s, a period during which the variance of inflation declined. The alternative measures of potential output for Chile are also estimated.